Use of Digital Twin Technology in the Teaching-Learning Process, in the field of University Education: A Bibliometric Review - Chamorro-Atalaya, Omar; Flores-Velásquez, Carlos Hernán; Flores-Cáceres, Richard; Arévalo-Tuesta, José Antonio; Zevallos-Castañeda, Milton; Tomás-Quispe, Gregório; Aranda-Dextre, Carmen Cristina; Cruz-Telada, Yreneo; Caller-Luna, Juan; Alarcón-Anco, Ronald (International Journal of Learning, Teaching and Educational Research, 2024)
At the convergence of artificial intelligence with pedagogy, digital twin technology is emerging as a tool that offers advanced simulations and interactive learning environments. This is because digital twins make it possible to replicate virtually any piece of equipment or test items in a laboratory. Based on the above, the objective of this article is to explore thematic gaps regarding the use of digital twin technology in the teaching-learning process. For this reason, a bibliometric review study is developed taking as data publications indexed in Scopus, during the years 2018 to 2023. Through the search equation, 92 publications were extracted. The study was developed under a quantitative approach at an exploratory-descriptive level. The results demonstrated that there is a growing and sustained scientific production on the topic under study, showing that, during and after the COVID-19 pandemic, there was greater production compared to other years. Furthermore, although it was identified that this technology is applicable to different specialties of higher education, it was determined that, to a greater extent, the topics discussed are engineering education assisted by digital twins, virtual reality and digital twins for engineering training and simulation-based training through digital twins. However, it is concluded that there is an unaddressed gap regarding the rules and regulations that should govern the use of digital twins in higher education as well as what the teacher's competencies should be so as to guarantee the appropriate use of digital twins as part of their teaching methodology, since the impact on student learning depends on this.